Dynamic properties of bolted joints in laminated composites evaluated using flexural wave propagation. (September 2018) - Kwak, Yunsang; Park, Sang Mok; Park, Junhong
Highlights: A method to measure the dynamic properties of the joint on composites was presented. The wave approach was used to analyze interactions between structures and joints. Wave propagation on the joints was predicted by dynamic stiffness and loss factor. The dynamic properties of the joints were derived for different clamping forces. Abstract: In this study, a method to evaluate the dynamic properties of bolted joints in laminated composites is proposed. The propagation of flexural waves through the joint was used to identify the joint stiffness. Experiments were performed by using carbon fiber/epoxy specimens. The specimens were fastened by a single-lap bolted joint. Vibration responses were measured for specimens fastened using different clamping forces. The dynamic properties of the joint were evaluated using translational and rotational complex joint stiffnesses. The predicted effects of the joint on the system vibration properties were compared to the measurements. A numerical method was proposed to calculate the dynamic properties. The stiffness and loss factor were derived to find the effects of the clamping forces. The evaluated stiffness was close to the predicted static stiffness. The joint loss factor was larger than that of the composite itself. With the increasing clamping forces, the stiffness increased and the loss factor decreased. The proposed method allows non-destructive continuous monitoring of a clamped part with additional information about the vibration reduction capability.